A comparison of upper-extremity reaction forces between the Yurchenko vault and floor exercise - Seeley, M. K.; Bressel, E. (Journal of Sports Science & Medicine, 2005)
The purpose of this study was to examine reaction forces transmitted to the upper extremities of high-level gymnasts during the round-off phase of the Yurchenko vault. A secondary purpose of this study was to compare reaction forces during the Yurchenko vault to reaction forces observed in a tumbling pass during the floor exercise. Ten high-level, female gymnasts volunteered to participate. Conditions of the independent variable were the Yurchenko vault and floor exercise; dependent variables were peak vertical and peak anterior-posterior reaction forces. Each participant performed three trials of both conditions with the trail hand contacting a force platform. Vertical and anterior-posterior reaction forces, normalized to body weight, were greater (p < 0.05) during the round-off phase of the Yurchenko vault (2.38) than during the floor exercise round-off (2.15). Vertical reaction forces during the round-off phase of the Yurchenko vault and floor exercise round-off are similar to reaction forces transmitted to upper extremities during other gymnastic skills and ground reaction forces transmitted to lower extremities while running and walking at various speeds. Results of this study reveal a need for further research considering methods aimed at reducing reaction forces transmitted to the upper extremities during the Yurchenko vault and floor exercise.